2005
DOI: 10.1007/s00213-005-2191-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caffeine on cognitive task performance and motor fatigue

Abstract: Caffeine improved cognitive performance. This effect also extends under demanding situations, as was shown by the performance during the dual task, even during progressive motor fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
51
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 38 publications
9
51
2
1
Order By: Relevance
“…This strengthens the assumption that the observed effect of caffeine within the frontal cortex was of a neuromodulatory sort. In contrast to several other psychopharmacological studies [7,8,10,76], no significant caffeine-related behavioral effects were observed. The researchers argued that this difference could be due to the rather low dosage of caffeine used in this study, which was chosen to avoid physiological side effects noticeable to the volunteers, as well as to reflect caffeine intake of common drinking habits.…”
Section: Imaging the Effects Of Caffeine On Cognitioncontrasting
confidence: 96%
See 1 more Smart Citation
“…This strengthens the assumption that the observed effect of caffeine within the frontal cortex was of a neuromodulatory sort. In contrast to several other psychopharmacological studies [7,8,10,76], no significant caffeine-related behavioral effects were observed. The researchers argued that this difference could be due to the rather low dosage of caffeine used in this study, which was chosen to avoid physiological side effects noticeable to the volunteers, as well as to reflect caffeine intake of common drinking habits.…”
Section: Imaging the Effects Of Caffeine On Cognitioncontrasting
confidence: 96%
“…Nevertheless, caffeine has been found to enhance task performance through increase of a) cortical activation, b) the rate at which information about a stimulus accumulates, c) selectivity to further processing of the primary attribute, and d) speed of motor processes via central or peripheral mechanisms [6]. It is not clear yet whether the observed beneficial effects on learning, memory, and performance derive from a direct enhancement of specific cognitive functions or can be attributed to increasing of arousal and overcoming fatigue [7][8][9][10].…”
mentioning
confidence: 99%
“…In addition, psychostimulants, such as caffeine, are usually thought of as nootropics [e.g. 15,26,49]. This folklore is exemplified by the advertisement campaign of the original Coca-Cola that contained cocaine, declaring it "the brain tonic and intellectual sodafountain beverage" [51].…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine doses in the range of 3-6mg*kg -1 are considered to be optimum for ergogenic effects in both physical (5) and psychological (22,23,24) tasks whilst minimising any adverse side effects of caffeine ingestion.…”
Section: Introductionmentioning
confidence: 99%